HUBUNGAN SIKAP PETANI KARET DENGAN PENGOLAHAN KARET MENJADI SHEET ANGIN DI KECAMATAN JAMBI LUAR KOTA KABUPATEN MUARO JAMBI - Suandi; Raga Sinaga, Muhammad; Farida, Aulia (Universitas Jambi, 2019)
The purpose og this research is to understand the attitude and rubber’s process to become rubber unsmoked sheet and to analyze the cross-sectional between farmer’s attitude toward the rubber’s process for rubber unsmoked sheet in Muhajirin village, Jambi Luar Kota, Muaro Jambi. The place was purposely selected with consideration that Jambi Luar Kota is the area that getting help to do the rubber unsmoked sheet process in Muaro Jambi Regency. This research is started since October 24, 2015 until November 24, 2015. The sample of this researc were 42 rubber farmers from 2 farmers group, using simple random sampling method. The data that being used were primary and secondary data. The primary data obtained from the farmers sample through the direct interview using the prepared question list, secondary data is taken from the departement or related agency or institute and literature which is related to this researc. The data that obtained from respondents were analyzed by statistic non-parametric, using the Ranks Spearman’s test. The result of this research shows that thitung > ttabel that contained a real connection toward the rubber’s process to become rubber unsmoked sheet with value 6,2771. The meaning of, the attitudes background on cognitive component, affective and conative have contained a real connection toward the rubber’s process to become rubber unsmoked sheet are 70,4 percent.